Generalized Additive Functional Equation: General Solution and Hyers-Ulam Stability in Banach Spaces via Alternative Fixed Point Theorem - Kandhasamy Tamilvanan; Syed Abdul Mohiuddine (Dera Natung Government College Research Journal)
In this paper, we secure the general solution of the generalized additive functional equation